2015
DOI: 10.1016/j.bbamem.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol strongly affects the organization of lipid monolayers studied as models of the milk fat globule membrane: Condensing effect and change in the lipid domain morphology

Abstract: The biological membrane that surrounds the milk fat globules exhibits phase separation of polar lipids that is poorly known. The objective of this study was to investigate the role played by cholesterol in the organization of monolayers prepared as models of the milk fat globule membrane (MFGM). Differential scanning calorimetry and X-ray diffraction experiments allowed characterization of the gel to liquid crystalline phase transition temperature of lipids, Tm ~35°C, in vesicles prepared with a MFGM lipid ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 33 publications
14
75
0
Order By: Relevance
“…The characterization of high-Tm lipid rich domains below 35°C is also in agreement with previous studies performed with dried Langmuir-Blodgett monolayers [8,9]. By using the same MFGM lipid extract at 20°C, Murthy et al [8] showed the formation of liquid-condensed domains composed of high-Tm milk polar lipids protruding by about 1.5 nm from the liquid expanded phase composed by unsaturated phospholipids. By using milk phospholipids extracted from raw cream, other…”
Section: Thermotropic Behavior and Identification Of Lipid Phasessupporting
confidence: 74%
See 2 more Smart Citations
“…The characterization of high-Tm lipid rich domains below 35°C is also in agreement with previous studies performed with dried Langmuir-Blodgett monolayers [8,9]. By using the same MFGM lipid extract at 20°C, Murthy et al [8] showed the formation of liquid-condensed domains composed of high-Tm milk polar lipids protruding by about 1.5 nm from the liquid expanded phase composed by unsaturated phospholipids. By using milk phospholipids extracted from raw cream, other…”
Section: Thermotropic Behavior and Identification Of Lipid Phasessupporting
confidence: 74%
“…The MFGM polar lipid extract used in this study was the same as in Murthy et al [8,23] Q water and adjusted to pH 6.7 using NaOH 5 M. PIPES 10 mM buffer with NaCl 50 mM and CaCl 2 2 mM (purity  99%; Sigma) was also prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,27,3033 Although this system is powerful in providing the molecular detail, Langmuir monolayers of dipalmitoylphosphatidylcholine (DPPC) are frequently used models of eukaryotic cell membranes. Langmuir monolayers have been used previously for a variety of studies, detailing interactions of lipids with cholesterol, 34 phospholipids, fatty acids, 35 proteins, 36,37 and drugs. 3841 By measuring the surface pressure of a phospholipid monolayer as a function of area per molecule, it is possible to compare a compound’s ability to interact with the phospholipid monolayer and determine if it is affecting the rigidity of the monolayer or the packing of the phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, this technique has been used to bring new insight into the functional role of CHOL in milk polar lipids, used in the preparation of dairy emulsions, e.g., infant milk formulas. In particular, the role played by CHOL in the organization of biological membranes surrounding lipid droplets in milk, called the milk fat globule membrane (MFGM), has been recently investigated [30][31][32][33]. Accordingly, CHOL concentration facilitates the phase separation and reduces the mechanical resistance to rupture of coexisting phases in bilayer models of the MFGM.…”
mentioning
confidence: 99%